Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1093/jnci/djaa099
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Our Understanding of Ovarian Cancer Risk: The Role of Incomplete Pregnancies

Abstract: Background Parity is associated with decreased risk of invasive ovarian cancer; however, the relationship between incomplete pregnancies and invasive ovarian cancer risk is unclear. This relationship was examined using 15 case-control studies from the Ovarian Cancer Association Consortium (OCAC). Histotype-specific associations, which have not been examined previously with large sample sizes, were also evaluated. Methods A po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
(64 reference statements)
4
8
1
Order By: Relevance
“…Three large observational studies have previously looked into differential effects of childbirths on ovarian cancer histological subtypes 7,21,22 . All three studies found protective effects of childbirth on the risk of each major subtype of ovarian cancer subtype (ie, serous, mucinous, endometrioid and clear‐cell ovarian cancer), which also was found in our study.…”
Section: Discussionsupporting
confidence: 86%
“…Three large observational studies have previously looked into differential effects of childbirths on ovarian cancer histological subtypes 7,21,22 . All three studies found protective effects of childbirth on the risk of each major subtype of ovarian cancer subtype (ie, serous, mucinous, endometrioid and clear‐cell ovarian cancer), which also was found in our study.…”
Section: Discussionsupporting
confidence: 86%
“…Some studies have observed that the risk of ovarian cancer decreases with the number of pregnancies. 23 , 24 We intended to analyze the relationship between the number of pregnancies and BRCA mutations in the patients with ovarian cancer. Accordingly, 8 women (4.1%) never had a pregnancy, 94 women (48.2%) had 1–3 pregnancies, 34 women (17.4%) had 4–5 pregnancies, 14 women (7.2%) had >5 pregnancies, and the remaining 45 (23.1%) were unknown.…”
Section: Resultsmentioning
confidence: 99%
“…The risk reduction observed in incomplete pregnancy (duration approximately 4-8 weeks) was similar in magnitude to the reduction observed with oral contraceptive use for 1 year (∼8% risk reduction per year of oral contraceptive use) ( 24 , 26 ), suggesting that factors present in pregnancy other than hormonal changes contribute to the protective effect of pregnancy. Another recent pooled study also showed a 16% reduction in ovarian cancer risk in women ever having an incomplete pregnancy ( 46 ), and another recent study reported that the reduced risk of ovarian cancer associated with term pregnancy was similar to the reduction with incomplete pregnancy including abortions ( 47 ). Taken together, these studies suggested that the incessant ovulation hypothesis may not be able to completely explain the mechanism underlying the protective effect of pregnancies.…”
Section: Evidence Of Flaws In the Altered Endocrine Balance Hypothesismentioning
confidence: 86%
“…A number of studies recently reported that women with incomplete pregnancies, such as spontaneous miscarriage or induced abortion, also have a reduced risk of developing ovarian and endometrial cancer despite progesterone levels only rising modestly compared with full term pregnancies ( 20 , 26 , 46 ). In a pooled analysis of 11 cohort and 29 case–control studies, incomplete pregnancies were found to reduce the risk of endometrial cancer, and to further reduce the risk by 7% to 9% for each additional incomplete pregnancy ( 26 ).…”
Section: Evidence Of Flaws In the Altered Endocrine Balance Hypothesismentioning
confidence: 99%